Food allergen sensitization patterns in psoriasis patients - A. A. Barilo; S. V. Smirnova; A. A. Sinyakov (Бюллетень сибирской медицины)
Background. Psoriasis is a chronic relapsing systemic disease characterized by inflammation in the skin. Etiology of psoriasis remains elusive, since there are many factors triggering a pathological process in the skin. Data on the frequency of allergies in patients with psoriasis are extremely few and contain conflicting results in the literature, which determines the relevance of the study. Researchers described coexisting atopic dermatitis (AD) and psoriasis (PS), which does not exclude common causes and mechanisms leading to skin damage. Aim. To study and conduct a comparative analysis of food allergen sensitization patterns in patients with psoriasis and atopic dermatitis. Materials and methods. A prospective study included patients with psoriasis (group 1, n = 51) and atopic dermatitis (group 2, comparison group, n = 20) aged 18–57 years. A control group (group 3, n = 19) encompassed apparently healthy sex- and age-matched individuals. Specific allergy testing included allergy history and determination of sensitization patterns by analyzing serum concentrations of total immunoglobulin E (IgE) and allergen-specific IgE (sIgE) to food allergens using ELISA test systems (Alkor-Bio, Russia) on the Thermo Scientific Multiskan FC microplate photometer. The calculation and analysis of the obtained data were carried out using the Statistica 8.0 software package. Results. The concentration of total immunoglobulin E in the blood serum for PS patients was 57.9 [31.6; 135.1] IU / ml, for AD patients – 210.4 [56.2; 1,000.0] IU / ml, and for the control group – 45.1 [23.4; 144.0] IU / ml, respectively, р1, 2 = 0.005; р2,.3 = 0.001; р1, 3 = 0.4. Food allergen sensitization was determined significantly more often in the group of AD patients compared to the group of PS patients: 95.0 (n = 19) vs. 37.2% (n = 19), respectively, р1, 2 = 0.005. In the group of AD patients, sensitization to chicken eggs, tomatoes, and peanuts was found significantly more frequently than in the group of PS patients and in the control group. Sensitization to beef, buckwheat, and potatoes was significantly more common in the group of PS patients than in the controls. Conclusion. Following the study of the serum concentration of allergen-specific IgE (sIgE) to food allergens, we revealed food allergen sensitization not only for AD patients, but also for PS patients. However, in our study, sensitization patterns to the studied allergens have their own characteristics depending on the specific disease.